Motivations of Israeli physicians to return, or not, to Israel after their fellowship abroad - Lior Seluk; Daniel Weltsch; Gadi Segal; Mayan Gilboa (BMC, 2024)
Abstract Background Emigration of healthcare professionals, particularly physicians, is an unresolved "pandemic", influenced by various factors. In high-income countries, the training phase (fellowship) abroad is critical for career development, yet it poses challenges for the retention of these professionals upon their completion of training. This study aimed to identify the determinants influencing Israeli physicians' decisions to return to their home country after completing fellowship training abroad. Methods This cross-sectional study conducted in early 2024, surveyed Israeli physicians with post-graduate training who pursued a fellowship abroad between 2013 and 2024. An anonymous survey included questions on demographics, training experience, and professional challenges. Analytical methods included descriptive statistics and regression analysis to explore factors associated with the decision to return. Results Of the 323 individuals surveyed, 297 met the inclusion criteria. Among them, 141 (47.5%) have returned to Israel, while 156 (52.5%) currently reside abroad, 48 (31%) of them have completed their fellowship. Respondents identified several challenges, beginning with a complex application process prior to fellowship (47% stated this as a major challenge), substantial financial burdens averaging 35,546 USD in direct out-of-pocket expenses during, and job uncertainty, with only 55% having secured positions upon return. Of the 156 Israeli fellows still abroad, 107 (69%) reported medium to low confidence in returning. Factors associated with a higher likelihood of confidence in returning to Israel included a secured job position upon return (OR 8.6, 95% CI 3.1-28.9) and having an opportunity for a position that would utilize the skills gained during the fellowship (OR 3.5, 95% CI 1.3-10.2). Conclusion The decision to return to Israel after a fellowship abroad is influenced by a mix of professional, personal, and geopolitical factors. To counteract the critical issue of brain drain, it is essential to enhance occupational certainty for returning physicians. These findings highlight the urgent need for healthcare policies that provide robust support for returning professionals and address their specific challenges.